Ink Degradation and Its Effects on the Crack Formation of Fuel Cell Catalyst Layers. Issue 2 (12th January 2019) - Uemura, Suguru; Yoshida, Toshihiko; Koga, Maito; Matsumoto, Hidetoshi; Yang, Xiaoqi; Shinohara, Kazuhiko; Sasabe, Takashi; Hirai, Shuichiro
Abstract : The catalyst layer (CL) in a proton exchange membrane fuel cell is a critical component that determines the performance of the cell. Although the CL is fabricated using a catalyst ink, there have been no studies concerning the effect of the quality of the ink on the CL structure. In the present work, catalyst ink samples were analyzed using gas chromatography-mass spectrometry. The results indicate the formation of hydrophobic compounds from the alcohol in the solvent, due to catalysis by Pt. These products result in the agglomeration of Pt/C particles, thus initiating cracks in the CL during the drying process.